Use of Nonideality Parameters for the Analysis of the Thermodynamic Properties of Binary Mixtures - Caroli-Rezende, M; Vidal-Palomo, M; Vidal-Palomo, M; Morales-Lovera, S (American Chemical Society, 2021)
Two parameters are introduced, a nonideality index (NII) and a nonideality area (NIA), for the analysis of the variations of thermodynamic properties of binary mixtures. Their calculation is based, for the NII, on experimental plots of the variation of a given property (density, refractive index, viscosity, etc.), and for the NIA, on experimental plots of its excess value (excess enthalpies, molar volumes, viscosities, refractive indices, isentropic compressibilities, etc.) with the mixture composition. Both nonideality parameters are therefore not based on any theoretical model or on its derived parameters, being applicable with any fitting equation. The NII or NIA values for a thermodynamic property of a series of related binary mixtures reveal interesting trends, which are not evident in most analyses of such systems. Besides their predictive value, these trends provide information on the relevance of solvent characteristics of the binary mixture, thus supporting new insights or interpretations of the experimental data. © 2021 The Authors. Published by American Chemical Society.